ChemInform Abstract: Generation of Ynolates via Reductive Lithiation Using Flow Microreactors. Issue 33 (19th August 2014) - Umezu, Satoshi; Yoshiiwa, Toshiya; Tokeshi, Manabu; Shindo, Mitsuru
Abstract The in situ generated ynolates are subsequently reacted with carbonyl compounds.